Data and code related to "Molecular kinetics dictate population dynamics in CRISPR-based plasmid defense" - Jones, Daniel; Richards, Luke; Lee, Danna; Wiktor, Jakub; Truedson, Axel; Cederblad, Johanna (Uppsala University, 2026)
Understanding and manipulating the spread of mobile genetic elements (MGEs) represents a great challenge with potential benefits across synthetic biology, agriculture and medicine. In this study, we use a time-lapse, imaging-based approach to characterize conjugative plasmid dynamics at the molecular, single-cell, and population levels.

This Dataset contains code used for image analysis, bioinformatic analysis, agent-based modelling, and figure generation for "Molecular kinetics dictate population dynamics in CRISPR-based plasmid defense", as well as intermediate single-cell data processed from raw images. See link to the publication in Related Material. Raw image data is included in the linked BioImage archive repository.

Specifically, the image analysis code contained here performs segmentation, fluorescent dot detection, and cell classification to track conjugative plasmid population dynamics in microfluidic growth chambers. The bioinformatic analysis code performs a comparative analysis of CRISPR spacer and toxin-antitoxin system presence across a broad range of bacterial plasmids.

Finally, the agent-based simulation code facilitates simulations of plasmid population dynamics in bacterial populations. Using this code, we can simulate plasmid population dynamics using single-cell biophysical parameters as inputs, and directly compare with experimental imaging-based data.
Keywords: Population ecology; Microbial ecology; Systems biology; Cellular interactions (incl. adhesion, matrix, cell wall); Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi; Ecology; Ekologi